2014
DOI: 10.7862/rb.2014.83
|View full text |Cite
|
Sign up to set email alerts
|

Post flood drying of partition walls made of autoclaved aerated concrete and the changes in thermal conductivity

Abstract: POPOWODZIOWE WYSYCHANIE PRZEGRÓD WYKONANYCH Z BETONU KOMÓRKOWEGO I ZACHODZĄCE ZMIANY PRZEWODNOŚCI CIEPLNEJW niniejszym referacie przedstawiono wyniki dwóch kilkuetapowych eksperymentów przeprowadzonych na próbkach z betonu komórkowego o klasie gęstości 400 kg/m 3 . W obu eksperymentach próbki najpierw poddano intensywnemu działaniu ciekłej wody, następnie w pierwszym pomierzono parametry cieplne, zaś w drugim suszono próbki w warunkach laboratoryjnych, tj. w temperaturze ok. 20 0 C i wilgotności względnej ok. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The relationship defined in this part was used to determine the thermal conductivity coefficient of specimens of concrete initially fully immersed in water and then during drying out under laboratory conditions for 1, 2 and 3 months. It was found that the equilibrium moisture content of the concrete structure was reached only after three months of drying [39]. The results obtained prove the indisputable necessity to take into account the moisture content of partition structures when drawing up energy balances of buildings, because moisture processes have a strong influence on the thermal parameters of walls.…”
Section: Research On Thermal Conductivity Of Autoclaved Aerated Concretementioning
confidence: 81%
See 1 more Smart Citation
“…The relationship defined in this part was used to determine the thermal conductivity coefficient of specimens of concrete initially fully immersed in water and then during drying out under laboratory conditions for 1, 2 and 3 months. It was found that the equilibrium moisture content of the concrete structure was reached only after three months of drying [39]. The results obtained prove the indisputable necessity to take into account the moisture content of partition structures when drawing up energy balances of buildings, because moisture processes have a strong influence on the thermal parameters of walls.…”
Section: Research On Thermal Conductivity Of Autoclaved Aerated Concretementioning
confidence: 81%
“…Garbalińska & Bochenek [39] present the results of two multi-step experiments in which measurements were made on specimens of autoclaved aerated concrete with a density of 400 kg/m 3 . One part of the experiment was to determine the empirical dependence of the thermal conductivity coefficient of autoclaved aerated concrete as a function of its moisture content.…”
Section: Research On Thermal Conductivity Of Autoclaved Aerated Concretementioning
confidence: 99%
“…Wstępne wyniki dotyczące pojedynczych, wybranych próbek betonu komórkowego klasy 400 prezentowane były wcześniej w artykule [4]. Tabela 1.…”
Section: Ocena Zmienności Parametrów Cieplnych W Procesie Wysychaniaunclassified